2009
DOI: 10.1080/09513590903015478
|View full text |Cite
|
Sign up to set email alerts
|

Serum visfatin in Asian women with polycystic ovary syndrome

Abstract: Asian PCOS women had significantly higher serum visfatin levels than age-matched healthy controls. Their levels were significantly correlated with 2hPG and blood pressure in PCOS women, and with FI and blood pressure in PCOS women with AGT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…However, if we removed adiponectin from the equation, this model was not significant (p = 0.067) and the R value was less (R = 0.543). DBP provided a positive impact on serum visfatin, which agreed with a previous finding of a positive association between serum visfatin levels and DBP [21].…”
Section: Discussionsupporting
confidence: 92%
“…However, if we removed adiponectin from the equation, this model was not significant (p = 0.067) and the R value was less (R = 0.543). DBP provided a positive impact on serum visfatin, which agreed with a previous finding of a positive association between serum visfatin levels and DBP [21].…”
Section: Discussionsupporting
confidence: 92%
“…In patients with PCOS from this study, visfatinaemia was positively related to free testosterone levels. In the previous reports, the findings on the topic were contradictory with circulating visfatin levels related either positively 7,8,31 or inversely 32 to androgen excess, expressed either as total or free testosterone or as the free androgen index. Occasionally, no relationship between testosterone and visfatin was found whatsoever 1,33 .…”
Section: Discussionmentioning
confidence: 93%
“…Over the past decade, some studies have investigated the visfatin levels in women with PCOS; in addition, the relationships between visfatin and PCOS characteristics, such as adiposity, IR and androgen levels, have also been the subject of research [8,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Yet, these studies have shown conflicting results.…”
Section: Introductionmentioning
confidence: 99%